Influence of hydrography on the spatiotemporal variability of phytoplankton assemblages and primary productivity in Funka Bay and the Tsugaru Strait. (15th March 2017) - Isada, Tomonori; Hirawake, Toru; Nakada, Satoshi; Kobayashi, Tsukuru; Sasaki, Ken'ichi; Tanaka, Yoshiyuki; Watanabe, Shuichi; Suzuki, Koji; Saitoh, Sei-Ichi
Abstract: Phytoplankton community structures and primary productivity were assessed in relation to the oceanographic conditions in the coastal waters of Funka bay and the eastern end of the Tsugaru Strait, adjacent to southwestern Hokkaido, Japan, from April 2010 to January 2012. Phytoplankton community compositions, as estimated from chemotaxonomic analysis based on high-performance liquid chromatography of pigments, showed diatom blooms during spring in both 2010 and 2011. However, spatial heterogeneity of chlorophyll a (Chl a ) concentration and primary productivity were found between regions investigated within and outside of Funka Bay during the spring diatom blooms in April 2010. The low Chl a concentrations within Funka Bay in April 2010 were related to the depletion of dissolved inorganic macronutrients, which implies that this difference was related to both the small inflow of the cold Coastal Oyashio Current (COW) into the bay and the development of clockwise circulation caused by discharge of fresh water into the bay. After the spring diatom blooms, the major phytoplankton groups in the study area were Chl b -containing phytoplanktons (chlorophytes and prasinophytes) because of changes in salinity associated with river discharge during the melting season. The results indicate that these phytoplanktons play an important role in the carbon cycle after the spring bloom in Funka Bay and the eastern end of the Tsugaru Strait. The thermohaline fronts created by the COW and the Tsugaru Warm Water in late February produced north–south differences in phytoplankton community structures in the eastern end of the Tsugaru Strait. Diatoms with high Chl a concentrations dominated in the northern section of the front. In the southern section, the proportions of chlorophytes and cryptophytes were high. Increases in cyanobacterial abundance and temperature were detected in both regions. Additionally, the contribution of pico- plus nano-sized phytoplankton productivity to the total primary productivity at the surface was concomitant with increases in temperature. Our results suggest that small-sized phytoplankton become more important part of the food web during summer, even in the coastal waters.